Bofutsushosan (Fangfengtongshengsan) improves early stages of NASH via the gut-liver axis in diabetes-induced NASH model mice - Mitsue Nishiyama; Shiori Ishizawa; Akinori Nishi; Akinobu Taketomi; Toru Kono (Elsevier, 2024)
Background: The mechanisms underlying non-alcoholic fatty liver disease (NAFLD) are not fully understood, but the gut microbiota is deeply involved. Because the Japanese traditional medicine bofutsushosan (BTS; Fangfengtongshengsan in Chinese) is known to improve obesity-induced liver injury and increase gut Akkermansia muciniphila, we evaluated its effects in a mouse model of diabetes-induced nonalcoholic steatohepatitis (NASH). Methods: Two-day-old male C57BL/6J mice were injected subcutaneously with streptozotocin and fed a high-fat diet (HFD) from 4 weeks. Between 5 and 8 weeks, HFD was supplemented with 5% BTS (BTS) or not supplemented (CONT), and plasma, liver, and stool samples were collected and analyzed. Results: The NAFLD activity score (NAS), which was consistent with early steatohepatitis in CONT mice, was significantly lower in BTS mice (P = 0.018). Improvement of steatosis contributed most to decreasing NAS. Relative abundances of probiotic Akkermansia muciniphila and Bifidobacterium pseudolongum were significantly higher in BTS mice (both P < 0.05). Positive correlations were observed among NAS, steatosis, ballooning, and body weight change. Liver macrophage markers correlated with some microbes in BTS mice. Conclusions: BTS administration suppressed liver steatosis and improved the gut microbiome, which correlated with some liver factors. BTS may be a promising treatment for NAFLD by maintaining the gut-liver axis.